Main directions of judicial reform: results and further modernization of the judicial system (Journal of actual problems of jurisprudence, 2020)
The goals of modernization of the judicial system of the Republic of Kazakhstan are determinedthrough the stages of judicial reforms, which consistently put forward certain requirements to the organizationand activity of the judicial system and judges. It must be acknowledged that the past decadehas seen tremendous innovations that have affected the quality of justice. Nevertheless, improving thequality of justice is an inexhaustible benchmark of judicial reforms, as the court, and its social and legalimportance in the society, determines the state of public and state-legal institutions, as well as the levelof maturity of democracy in the state.In this sense, we are looking for new opportunities to achieve the results. One of the latest breakthroughsin this direction is the introduction of a project management system in the development of newcommunicative approaches, which has proved its relevance and timeliness.Nevertheless, as the analysis of the results of the event shows, this kind of communication shouldbe accompanied by scientific and legal comments, research, etc. To date, the success of judicial reformsdepends not only on the participation of the large number of professionals from the judicial communitybut also the representatives of other professions directly related to the judicial process. As part of thescientific and legal assessment of certain practical proposals, it is possible to identify or create opportunitiesand ways of their implementation, which determines the overall effectiveness of the process ofmodernization of the judicial system of the Republic of Kazakhstan.Key words: modernization, judicial system, reform, qualification, judicial process.